Transcutaneous Auricular Vagus Nerve Stimulation (taVNS) for Insomnia Disorder: A Narrative Review of Effectiveness, Mechanisms and Recommendations for Clinical Practice - Liu C; Chen S; Zhang Y; Wu X; Liu J (Nature and Science of Sleep)
Chenshi Liu,1,2 Shiyin Chen,1,3 Yuwen Zhang,2,4 Xiao Wu,1,3 Jie Liu1,2 1Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 2Department of Neurology, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 3Department of Chinese Medicine, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China; 4School of Clinical Medicine, Southwest Medical University, Luzhou, People’s Republic of ChinaCorrespondence: Jie Liu, Department of Neurology, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China, Email liujiesyy@126.com Xiao Wu, Department of Chinese Medicine, Sichuan Provincial People’s Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People’s Republic of China, Email wuxiaozy@med.uestc.edu.cnAbstract: Insomnia disorder is a very common disease that has received widespread attention in modern society, but the effects of current treatments for insomnia disorder are far from satisfactory. Transcutaneous auricular vagus nerve stimulation (taVNS) is a safe and highly tolerated method, and it might be an alternative therapy for patients with insomnia disorder. This narrative review synthesizes clinical and mechanistic evidence of taVNS for insomnia disorder, critically analyzing its multimodal therapeutic actions from the perspectives of brain networks modulation, neurotransmitter-hormone axis regulation, anti-inflammatory effects, and changes in autonomic nerve function. Existing studies have shown that taVNS can improve sleep quality, quality of life and the accompanying negative emotions. However, the deficiencies in the current trial methods may lead to a reduction in the quality of evidence. Although existing findings support taVNS as a promising strategy for treating insomnia, more high-quality trials are needed to verify its benefits and elucidate its mechanisms of action.Keywords: insomnia disorders, transcutaneous auricular vagus nerve stimulation, vagus nerve, mechanism, brain network, autonomic nervous function